2020
DOI: 10.1186/s12882-020-02070-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dialysis modality choice on the survival of end-stage renal disease patients in southern China: a retrospective cohort study

Abstract: Background The optimal choice of treatment, with hemodialysis (HD) or peritoneal dialysis (PD), for end-stage renal disease (ESRD) patients, is still controversial. Only a few studies comparing HD and PD have been conducted in China, which has the largest number of dialysis patients in the world. Methods A retrospective cohort study was conducted on ESRD patients who began renal replacement treatment from January 1, 2012 to December 31, 2017 in Guangdong Provincial Hospital of Chinese Medicine. Propensity sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
0
16
1
Order By: Relevance
“…Subgroup analyses were performed with respect to age. Previous studies ( 15 ) suggested that patients undergoing HD and PD have different prognoses in different age subgroups. Therefore, we used a Cox regression model to confirm the interactive effect of age and dialysis type.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subgroup analyses were performed with respect to age. Previous studies ( 15 ) suggested that patients undergoing HD and PD have different prognoses in different age subgroups. Therefore, we used a Cox regression model to confirm the interactive effect of age and dialysis type.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies at our center have shown that the prognoses of PD and HD are different for end-stage renal patients at different ages ( 15 ). We hypothesize that the prognosis of ESRD patients with CHF receiving different dialysis methods may be different.…”
Section: Introductionmentioning
confidence: 96%
“…A 10‐year cohort study of elderly ESRD patients, in Taiwan, showed a mortality of 354.30/1000 person‐years in hemodialysis patients and 152.04/1000 person‐years in non‐hemodialysis patients 11 . A previous study in Guangdong, China, reported that the 5‐year survival rate of ESRD patients was over 70%, and the survival of elderly patients was significantly lower than that of younger patients 12 . With the development of diagnosis and treatment technology, the survival probability of patients has improved, and the survival time has been continuously extended, but there is still a lack of survival estimation of ESRD patients treated for more than 10 years in China.…”
Section: Introductionmentioning
confidence: 99%
“…In dialysis treatment, the elderly and younger ESRD patients need to face different dilemmas. Older patients may suffer from poor physical health due to more comorbidities, which affects their treatment regimen and medical expenses and increases the risk of mortality, while young and middle‐aged patients may have poor survival status owing to their more social participation and economic burden 12,23 . Therefore, patients with ESRD were divided into three groups (young, middle‐aged, and elderly) in this study, for stratified comparison.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the quality of life for a CKD patient is better when undergoing PD than HD [6]. A retrospective cohort study showed that PD is considered a better choice of KRT in young patients [7]. A survey of Saudi ESKD patients undergoing HD suggested that their refusal of PD is related to a lack of prior and adequate counseling and education about PD [8].…”
Section: Introductionmentioning
confidence: 99%